Multiview RT3D Echocardiography Image Fusion - Rajpoot, K; Noble, J; Grau, V; Szmigielski, C; Becher, H (2009)
Real-time three-dimensional echocardiography (RT3DE) permits the acquisition and visualization of the beating heart in 3D. However, its actual utility is limited due to missing anatomical structures and limited field-of-view (FOV). We present an automatic two-stage registration and fusion method to integrate multiple single-view RT3DE images. The registration scheme finds a rigid transformation by using a multiresolution algorithm. The fusion is based on the 3D wavelet transform, utilizing the separation of the image into low- and high-frequency wavelet subbands. The qualitative and quantitative results, from 12 subjects, demonstrate that the proposed fusion framework helps in: (i) filling-in missing anatomical information, (ii) extending the FOV, and (iii) increasing the structural information and image contrast. © 2009 Springer Berlin Heidelberg.